2016
DOI: 10.3844/ajessp.2016.341.357
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Heavy Metals in Fish in Saudi Arabia

Abstract: Heavy metals such as arsenic, cadmium, mercury and lead constitute a serious threat to human health. Generally, regular consumption of fish is recommended because it is a good source of omega-3 fatty acids, which have been associated with health benefits. However, flesh of some fish species contains heavy metals in high concentration, which may pose health risk for individuals that consume them in significant quantities. Therefore, over the last few years, evaluation of heavy metals in fish has become a matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Moreover, exposure to heavy metals through dust is only one of the major human exposure pathways of the contaminants, other routes of exposure must be considered. In Saudi Arabia, drinking water, especially water wells [ 108 ], vegetables [ 109 ], fruits [ 110 ], cereals [ 111 ], spices and herbs [ 112 ], cow’s milk [ 113 ] and fishes [ 114 , 115 ] were reported to be contaminated with heavy metals in different levels. Therefore, human risk assessment studies based on all possible exposures are highly recommended in Saudi Arabia.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, exposure to heavy metals through dust is only one of the major human exposure pathways of the contaminants, other routes of exposure must be considered. In Saudi Arabia, drinking water, especially water wells [ 108 ], vegetables [ 109 ], fruits [ 110 ], cereals [ 111 ], spices and herbs [ 112 ], cow’s milk [ 113 ] and fishes [ 114 , 115 ] were reported to be contaminated with heavy metals in different levels. Therefore, human risk assessment studies based on all possible exposures are highly recommended in Saudi Arabia.…”
Section: Resultsmentioning
confidence: 99%
“…Fish consumption is a critical source of human exposure to mercury alongside dental amalgam use or occupational exposure [ 12 , 13 ]. A previous study reported that consuming fish from the Red Sea and Arabian Gulf potentially poses a health risk because of mercury bioaccumulation [ 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…Mean values of chromium in Carp and Cat fishes (Table 2) were observed to be lower than permissible limit of FAO (1983), EU (2008) and some literature values [52][53]. Chromium levels in the remaining fish samples were higher than the permissible limits above and those reported in Balistoides Vridiscens [19]. Bioaccumulation of chromium in humans can lead to; pulmonary fibrosis, lung cancer Moon fish = Carp fish (79.55).…”
Section: Resultsmentioning
confidence: 79%
“…Cadmium can remain in human system for decades and cannot be efficiently metabolized. It can cause kidney damage, lung cancer, testicular tissue destruction, high blood pressure, proteinuria, red blood destruction and non-descended testes in young males [19,[48][49]. Recent research show that exposure to cadmium at even low concentration can increase the risk of hormonal cancer [50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation